Experience with transverse preputial island flap for repair of hypospadias in Ile-Ife, Nigeria - Sowande A; Olajide A; Salako A; Olajide F; Adejuyigbe O; Talabi A (Wolters Kluwer Medknow Publications, 2009)
Objective: To review our experience with the use of transverse preputial island flap in the repair of hypospadias in the paediatric surgical unit of our University Teaching Hospital, Nigeria. Patients and Methods: We reviewed the cases of hypospadias managed by transverse preputial island flap repair over a ten year period (1996 and 2006) in the paediatric surgical unit of our institution. Data was retrieved from the case notes and analysed. Results: Fifty-one patients had hypospadias repair during the period, 22 of whom were by transverse preputial island flap repair. Hypospadisas were in penile shaft in 16 (72.7%), penoscrotal in 5 (22.7%) and perineal in 1 (4.55%). All the patients had intact prepuce at presentation and chordee was present in 18 (81.8%). The commonest complication was urethrocutaneous fistula in five patients, which closed spontaneously in three leaving 2 patients (9.1%) with persistent urethrocutaneous fistular. Conclusion: Transverse preputial island flap urethroplasty remains aviable option in the management of hypospadias especially when the meatal opening is proximal, with associated chordee limiting the options in the repair.